Motivasi Lansia Pria dalam Melakukan Olahraga Bulutangkis di Kecamatan Prambon, Kabupaten Nganjuk, Jawa Timur Tahun 2024: Motivation of Elderly Men in Playing Badminton in Prambon District, Nganjuk Regency, East Java, in 2024 - Thoriq Al Farah, Ahmad; Yuliawan, Dhedhy; Burstiando, Riski (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2025)
This study aims to analyze the motivation of elderly men in playing badminton in Prambon District, Nganjuk Regency, East Java. Motivation is a crucial factor in sustaining physical activity among the elderly, especially in high-intensity sports like badminton. This research employs a quantitative approach using a survey method with questionnaires. The study sample consists of 32 elderly men who actively play badminton. Data were analyzed using descriptive statistics to examine the trends in intrinsic and extrinsic motivation. The results indicate that intrinsic factors have the highest relative frequency in the "Very High" category at 34%, while extrinsic factors have the highest relative frequency in the "High" category at 38%. The findings conclude that elderly men's motivation to play badminton falls within the high and very high categories, with intrinsic factors being the primary driving force.